WAND User's Guide. - Gerritsen,Rob; Cortes,Ricardo; Ribeiro,Jim; Zowader,Ruth (1976)
This guide presents the basic concepts of WAND, a Database Management System. The first section presents the major concepts and terminology of WAND. It also introduces the Data Description Language (DDL) and the Data Manipulation Language (DML). The second section describes in detail the DDL and the procedures used to create the schema. The third section contains the DML statements and several examples illustrating their use. (Author)